A link between pH homeostasis and colistin resistance in bacteria - Pradip R. Panta (Nature Portfolio, 2021)
Abstract Colistin resistance is complex and multifactorial. DbcA is an inner membrane protein belonging to the DedA superfamily required for maintaining extreme colistin resistance of Burkholderia thailandensis. The molecular mechanisms behind this remain unclear. Here, we report that ∆dbcA displays alkaline pH/bicarbonate sensitivity and propose a role of DbcA in extreme colistin resistance of B. thailandensis by maintaining cytoplasmic pH homeostasis. We found that alkaline pH or presence of sodium bicarbonate displays a synergistic effect with colistin against not only extremely colistin resistant species like B. thailandensis and Serratia marcescens, but also a majority of Gram-negative and Gram-positive bacteria tested, suggesting a link between cytoplasmic pH homeostasis and colistin resistance across species. We found that lowering the level of oxygen in the growth media or supplementation of fermentable sugars such as glucose not only alleviated alkaline pH stress, but also increased colistin resistance in most bacteria tested, likely by avoiding cytoplasmic alkalinization. Our observations suggest a previously unreported link between pH, oxygen, and colistin resistance. We propose that maintaining optimal cytoplasmic pH is required for colistin resistance in a majority of bacterial species, consistent with the emerging link between cytoplasmic pH homeostasis and antibiotic resistance.